2022
DOI: 10.3389/fimmu.2022.733800
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dendritic Cell Function Within the Tumour Microenvironment

Abstract: The tumour microenvironment (TME) presents a major block to anti-tumour immune responses and to effective cancer immunotherapy. The inflammatory mediators such as cytokines, chemokines, growth factors and prostaglandins generated in the TME alter the phenotype and function of dendritic cells (DCs) that are critical for a successful adaptive immune response against the growing tumour. In this mini review we discuss how tumour cells and the surrounding stroma modulate DC maturation and trafficking to impact T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 193 publications
(221 reference statements)
0
23
0
Order By: Relevance
“…Although several preclinical studies have suggested an immunosuppressive function of mregDCs within the TME, reports are still lacking relating tumour‐infiltrating mregDCs with poor prognosis and immunotherapy resistance in cancer patients. 82 This phenomenon may be due to the lack of a unified definition standard for mregDCs, which has resulted in multiple and complex names in different studies; these names include LAMP3 + CCR7 + cells, CD45 + Lin − MHC‐II + CD11c + CD80 hi CD274 hi , and LAMP3 + IDO1 + CCL19 + cells. Furthermore, the annotation of mregDCs in single‐cell studies involves a series of genes, while previous relevant studies could not precisely define mregDCs due to the limitations of the experimental technology.…”
Section: Prognostic Value Of Mregdcs In Cancersmentioning
confidence: 99%
“…Although several preclinical studies have suggested an immunosuppressive function of mregDCs within the TME, reports are still lacking relating tumour‐infiltrating mregDCs with poor prognosis and immunotherapy resistance in cancer patients. 82 This phenomenon may be due to the lack of a unified definition standard for mregDCs, which has resulted in multiple and complex names in different studies; these names include LAMP3 + CCR7 + cells, CD45 + Lin − MHC‐II + CD11c + CD80 hi CD274 hi , and LAMP3 + IDO1 + CCL19 + cells. Furthermore, the annotation of mregDCs in single‐cell studies involves a series of genes, while previous relevant studies could not precisely define mregDCs due to the limitations of the experimental technology.…”
Section: Prognostic Value Of Mregdcs In Cancersmentioning
confidence: 99%
“…DCs are the initiator of the body’s immune response, and their primary characteristic is stimulation of primary T cell proliferation. The fibroblast matrix and the associated ECM around the tumor provide physical constraints on infiltrating DCs, and regulate DC maturation and trafficking, thereby influencing T-cell function 95 . Myelofibrosis is believed to promote the pathological remodeling of the ECM, and studies have confirmed that the physical and mechanical properties of myelofibrosis contribute to the abnormal differentiation of monocytes, thus causing proinflammatory polarization of monocytes and differentiation into DCs 96 .…”
Section: Mechanical Properties Of the Ecm And The Tumor Immune Microe...mentioning
confidence: 99%
“…OVs are also responsible for the activation of additional immune responses, which serve to counterbalance the decrease in the presentation of tumor antigens and to boost the interaction of APCs with T cells that are specific to the tumor ( 117 ). For instance, several soluble substances released in the TME, including IL-6, IL-10, IDO, M-CSF, transforming growth factor-β1 (TGF-β1), PGE2, and VEGF, can assist the immunosuppression of tumor-infiltrating DCs ( 118 ). IL-6 knockout mice ( 119 ), anti-VEGF antibodies ( 120 , 121 ), and anti-IL-8 monoclonal antibodies improved immune control in a series of animal models, resulting in an improved immune response to tumors ( 122 , 123 ).…”
Section: Dcs and Nk Cells As The Enhancer Of Ovsmentioning
confidence: 99%
“…IL-6 knockout mice ( 119 ), anti-VEGF antibodies ( 120 , 121 ), and anti-IL-8 monoclonal antibodies improved immune control in a series of animal models, resulting in an improved immune response to tumors ( 122 , 123 ). However, pro-inflammatory cytokines are also present in the TME, which helps to improve DC maturation, enhance antigen priming, and boost immune infiltration in malignancies ( 118 ). Consequently, the intricate balance of inflammatory signals in the TME is a topic of significant study interest but is currently difficult to focus.…”
Section: Dcs and Nk Cells As The Enhancer Of Ovsmentioning
confidence: 99%